2022
DOI: 10.1111/cid.13087
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of implant loss risk factors after simultaneous guided bone regeneration: A retrospective study of 5404 dental implants

Abstract: Purpose: The purpose was to analyze the risk factors for implant loss after simultaneous guided bone regeneration (GBR).Materials and Methods: Patients who underwent implant placement with simultaneous GBR between January 2011 and December 2018 were screened for this study. The cumulative survival rate (CSR) was calculated using the life table method.Log-rank test and Kaplan-Meier survival estimates were used to identify potential risk factors for implant loss. The association between the investigated variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…The general parameters, including age, gender, implant position, jaw position, smoking habits, and history of periodontitis, have been previously correlated with implant loss, 45 especially in bone augmentation procedures. 46,47 Therefore, multivariate analyses in terms of BW 1 , BW 2 , BV 1 , BV 2 , and BV% were conducted via GEE to adjust for potential confounding factors within intra-group differences. A 95% confidence interval was calculated for the measurements, and P < 0.05 was considered as a statistically significant result.…”
Section: Discussionmentioning
confidence: 99%
“…The general parameters, including age, gender, implant position, jaw position, smoking habits, and history of periodontitis, have been previously correlated with implant loss, 45 especially in bone augmentation procedures. 46,47 Therefore, multivariate analyses in terms of BW 1 , BW 2 , BV 1 , BV 2 , and BV% were conducted via GEE to adjust for potential confounding factors within intra-group differences. A 95% confidence interval was calculated for the measurements, and P < 0.05 was considered as a statistically significant result.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of risk drivers of peri‐implant diseases incidence and progression identified in studies are: Older age 99,135 Male sex 136 Autoimmune/inflammatory/rheumatoid/skin diseases, 128 especially Sjogren's syndrome 137,138 …”
Section: Impact Of Systemic Driversmentioning
confidence: 99%
“…99,135 • Male sex. 136 • Autoimmune/inflammatory/rheumatoid/skin diseases, 128 especially Sjogren's syndrome. 137,138 • Genetics/epigenetics.…”
Section: Other Potentially Systemic Driversmentioning
confidence: 99%
“…Implants placed with simultaneous GBR in the posterior mandibular region can achieve high survival rate and good peri‐implant bone stability 9 . However, our previous study showed that implant type may be associated with implant loss after simultaneous GBR 10 . Marginal bone loss (ΔMBL) around the implant is one of the important criteria for implant success, and can be detected earlier than implant loss after implant placement.…”
Section: Introductionmentioning
confidence: 99%
“…9 However, our previous study showed that implant type may be associated with implant loss after simultaneous GBR. 10 Marginal bone loss (ΔMBL) around the implant is one of the important criteria for implant success, and can be detected earlier than implant loss after implant placement. Numerous studies suggested that the ΔMBL of bone-level implants was significantly lower than that of tissue-level implants and had better long-term bone stability as well.…”
Section: Introductionmentioning
confidence: 99%